Meigs' syndrome and adult-type granulosa cell tumor - Szu-Ting Yang; Min Cheng; Chung-Ru Lai; Shu-Huei Shen; Wen-Ling Lee; Peng-Hui Wang (Elsevier, 2021)
Objective: Adult-type granulosa cell tumors (GCT) are sex cord-stromal tumors and often accompanied with abdominal distention and hyperestrogenism-related symptoms. Adult-type GCT-presenting ascites and pleural effusion is extremely rare. Case report: A 56-year-old perimenopausal woman presented with abdominal distention and abnormal vaginal spotting. Ultrasound and abdominal computed tomography showed a complex cystic mass in the left ovary accompanied with bilateral pleural effusion and ascites. The patient underwent total abdominal hysterectomy, bilateral salpingo-oophorectomy, left pelvic lymph node dissection, omentectomy and appendectomy. Final histopathological diagnosis was adult-type GCT. The patient had postoperative hormone and anti-angiogenesis agent therapy with free of disease. Conclusion: Ovarian cystic complex mass accompanied with ascites and pleural effusion often results from malignant ovarian tumors or benign ovarian fibroma. Based on the aforementioned report, the rare types of ovarian tumors, such as adult-type granulosa cell tumor of the ovary should be taken into consideration.